2014
DOI: 10.2478/umcschem-2013-0003
|View full text |Cite
|
Sign up to set email alerts
|

FT-IR/PAS Study of Surface EDTA-ZnO Interactions

Abstract: The interaction of EDTA disodium salt with zinc oxide was investigated by photoacoustic (PA) FT-IR. It was demonstrated that EDTA-III adsorbs on ZnO, and the process mimics behaviour of EDTA-oxide systems, in which IEPS of oxide catalytic supports is higher than 9. Model of the interaction, described in literature, was discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
(26 reference statements)
2
3
0
Order By: Relevance
“…Contrariwise, the presence of EDTA in the solutions stabilizes the pH of NaCl solutions during the discharge, as confirmed by the pH still close to 10 after the 24 h discharge experiments, due to complexing Zn 2 + ions before the other possible reactions that would consume OH À ions can take place. Furthermore, in accordance with previous studies, [48][49][50] EDTA can be adsorbed on the surface of ZnO or even leach the ions from the respective oxide or hydroxide, which adds up to the synergetic effects of addition of EDTA to the 2 M NaCl on discharge performance.…”
Section: Batteries and Supercapssupporting
confidence: 87%
See 2 more Smart Citations
“…Contrariwise, the presence of EDTA in the solutions stabilizes the pH of NaCl solutions during the discharge, as confirmed by the pH still close to 10 after the 24 h discharge experiments, due to complexing Zn 2 + ions before the other possible reactions that would consume OH À ions can take place. Furthermore, in accordance with previous studies, [48][49][50] EDTA can be adsorbed on the surface of ZnO or even leach the ions from the respective oxide or hydroxide, which adds up to the synergetic effects of addition of EDTA to the 2 M NaCl on discharge performance.…”
Section: Batteries and Supercapssupporting
confidence: 87%
“…[46,47] Moreover, previous studies have shown that EDTA is capable of leaching metal ions from oxides or hydroxides. [48][49][50] Hence, similar mechanisms could also be the origin of the EDTA influence on the Zn potentials shown in this study.…”
Section: Open Circuit Potential and Potentiodynamic Polarizationsupporting
confidence: 65%
See 1 more Smart Citation
“…Other smaller vibration bands observed are also the bands of the organic parts . High surface area of ZnO in nano scale facilitates EDTA adsorption …”
Section: Resultsmentioning
confidence: 89%
“…The peaks at 1396 and 1626 cm −1 are assignable to the CO vibration in neat EDTA from the COOH group assigned to the asymmetrical and symmetrical stretching . But in the case of modified ZnO‐EDTA, this peak with a slight shift to lower wavenumbers has been appeared at the 1578 cm −1 and 1412 cm −1 when bound to surfaces . The position of the carbonyl band in the infrared spectrum of EDTA complexes can be utilized as the indication of the nature of the M—O bond.…”
Section: Resultsmentioning
confidence: 99%